2009
DOI: 10.1590/s0004-282x2009000500034
|View full text |Cite
|
Sign up to set email alerts
|

Diretrizes para o manejo de pacientes com hemorragia intraparenquimatosa cerebral espontânea

Abstract: Resumo -A hemorragia intraparenquimatosa cerebral (HIC) é o subtipo de AVC de pior prognóstico e com tratamento ainda controverso em diversos aspectos. O comitê executivo da Sociedade Brasileira de Doenças Cerebrovasculares, através de uma revisão ampla dos artigos publicados em revistas indexadas, elaborou sugestões e recomendações que são aqui descritas com suas respectivas classificações de níveis de evidência. Estas diretrizes foram elaboradas com o objetivo de prover o leitor de um racional para o manejo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
24

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 97 publications
(96 reference statements)
0
9
0
24
Order By: Relevance
“…1 According to recent estimates, there is a tendency toward a progressive increase in the number of deaths from cerebrovascular diseases, and it is estimated that by 2030 the percentage will reach 12.1% of the world mortality. 2 Cerebral aneurysm consists of localized dilation of the vascular wall which, when ruptured, generates subarachnoid hemorrhage (SAH). 3 Most cerebral aneurysms are asymptomatic for a lifetime or until they rupture, and may progress to SAH, one of the serious events of its rupture.…”
Section: Introductionmentioning
confidence: 99%
“…1 According to recent estimates, there is a tendency toward a progressive increase in the number of deaths from cerebrovascular diseases, and it is estimated that by 2030 the percentage will reach 12.1% of the world mortality. 2 Cerebral aneurysm consists of localized dilation of the vascular wall which, when ruptured, generates subarachnoid hemorrhage (SAH). 3 Most cerebral aneurysms are asymptomatic for a lifetime or until they rupture, and may progress to SAH, one of the serious events of its rupture.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that hyperthermia (axillary temperature ≥37.5ºC) is treated in the acute phase of HIP usually with acetaminophen or dipyrone. In refractory cases, it may be associated with anti-inflammatory non-steroidal, external physical methods and internal active cooling (intravascular cooling catheters), although there are no studies proving efficacy and safety of cooling in patients with hemorrhagic stroke [1][2][3] .…”
Section: Temperaturementioning
confidence: 99%
“…According to the Brazilian Society of Cerebrovascular Diseases, hemorrhagic stroke is the whole event caused by spontaneous (non-traumatic) rupture of a vessel, with extravasation of blood to the inside of the brain (hemorrhage intraparenchymal), for the ventricular system (intraventricular hemorrhage) and/or subarachnoid space (subarachnoid hemorrhage) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…No AVE hemorrágico (AVEh) ocorre a ruptura espontânea de veias ou artérias promovendo um extravasamento de sangue (PONTES-NETO et al, 2009), podendo ser classificado em hemorragia intraparenquimatosa, quando o extravasamento é direcionado ao interior do cérebro, hemorragia intraventricular, quando se instala no sistema ventricular e hemorragia subaracnóidea quando se instala no espaço subaracnóideo (PONTES-NETO et al, 2009). Os episódios de AVEh representam cerca de 10-13% da totalidade dos casos de AVE (GO et al, 2014).…”
Section: Acidente Vascular Encefálico Hemorrágicounclassified
“…Nos países da América Latina, o índice de mortalidade relacionado as doenças cerebrovasculares chega a 80% (LOTUFO, 2005;LOTUFO;BENSEÑOR, 2009). No Brasil, a taxa de mortalidade ajustada com a idade é a maior da América Latina, tanto para homens quanto para mulheres (DUNCAN, 1994;LOTUFO, 2002;SRIDHARAN et al, 2009;BONITA et al, 2004;LOTUFO, 2005;LOTUFO;BENSEÑOR, 2009;PONTES-NETO, 2008 ROTHWELL et al, 2004;MYINT et al, 2008).…”
Section: Epidemiologiaunclassified